Minimal Morse functions on a pair of manifolds - Prishlyak, O. O. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The existence theorem for a minimal Morse function on a pair of manifolds (M_n,N_k), where n - k ≥ 3, k ≥ 6, is proved.